ŞAŞILIK CERRAHİSİ SONUÇLARI VE FÜZYONA ETKİSİ - DİKİCİ, Kemal and KIZILKAYA, Melda (Cerrahpaşa Medical Journal, 2014)
Background.. The purpose of this study is to investigate whether fusion develops after surgery in different strabismus types and to evaluate late results of the strabismus surgery. Design.- 46 male and 54 female; total of 100 cases were classified according to their deviation angles and refractive errors and fusion was measured. Results.- 24 (24%) right esotropia, 27 (27%) left esotropia, 5 (5%) right exotropia, 7 (7%) left exotropia, 11 (11%) alternating exotropia, 26 (26%) alternating esotropia cases were included in the study. We detected fusion postoperatively in four of the 38 cases who did not have fusion before. Two of the cases were alternating esotropia and the other two were alternating exotropia. Although postoperatively deviation angle improved in monocular strabismus cases who did not have fusion preoperatively, fusion did not develop in the follow-up. Four of the alternating esotropia cases had fusion preoperatively. In addition, one more case developed fusion postoperatively. Cases with consecutive esotropia and exotropia did not have fusion. Conclusion.- We think that with early surgical intervention in strabismus treatment, the chance of binocular vision development and success rate increases.